Studying cyto and myeloarchitecture of the human cortex at ultra-high field with quantitative imaging: R 1 , R 2 and magnetic susceptibility - Marques, José P; Khabipova, Diana; Gruetter, Rolf (NeuroImage (Orlando, Fla.), 2017)
In this manuscript, the use of quantitative imaging at ultra-high field is evaluated as a mean to study cyto and myelo-architecture of the cortex. The quantitative contrasts used are the longitudinal relaxation rate (R ), apparent transverse relaxation rate (R ) and quantitative susceptibility mapping (QSM). The quantitative contrasts were computed using high resolution in-vivo (0.65mm isotropic) brain data acquired at 7T. The performance of the different quantitative approaches was evaluated by visualizing the contrast between known highly myelinated primary sensory cortex regions and the neighbouring cortex. The transition from the inner layers to the outer layers (from white matter to the pial surface) of the human cortex, which is known to have varying cyto- and myelo architecture, was evaluated. The across cortex and through depth behaviour observed for the different quantitative maps was in good agreement between the different subjects, clearly allowing the differentiation between different Brodmann regions, suggesting these features could be used for individual cortical brain parcellation. While both R and R maps decrease monotonically from the white matter to the pial surface due to the decrease of myelin and iron between these regions, magnetic susceptibility maps have a more complex behaviour reflecting its opposing sensitivity to myelin and iron concentration.